Ameloblastic Fibroma of the Maxilla with Bilateral Presentation: Report of a Rare Case with Review of the Literature - Kranti Kiran Reddy Ealla; Vijayabaskar Reddy Basavanapalli; Surekha Reddy Velidandla; Sangameshwar Manikya; Rajesh Ragulakollu; Prasanna M. Danappanavar; Vijayasree Vennila (Case Reports in Pediatrics)
Ameloblastic fibroma (AF) is an uncommon benign odontogenic tumour, with both epithelial and mesenchymal neoplastic proliferation. It occurs most frequently in the posterior region of the mandible, while its occurrence in the maxilla is extremely rare. They are usually encountered in children, emphasizing it as an important diagnostic consideration. Herein, we report the first case of a bilateral maxillary ameloblastic fibroma in a 2-year-old female child patient who presented with a chief complaint of swelling in the right mid facial region.